(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This study aims to discuss the various studies belonging to happiness and to find out the definitions, its types and its relationships with other factors. The study would benefit an individual to understand how which and why different factors at different stages or aspects affect our happiness.